Effect of trichloroacetaldehyde on the activation of CD4+T cells in occupational medicamentosa-like dermatitis: An in vivo and in vitro study. (1st July 2019) - Li, Wenxue; Liu, Xiaoling; Yang, Xueqin; Chen, Yaping; Pang, Yaqin; Qi, Guangzi; Chen, Liping; Zhuang, Zhixiong
Abstract: Occupational medicamentosa-like dermatitis induced by trichloroethylene (OMLDT) is a hypersensitivity disease with autoimmune liver injury, which has increasingly become a serious occupational health problem in China. However, the pathogenesis of OMLDT remained undefined. In this study, 30 TCE-induced OMLDT patients, 58 exposure controls, and 40 non-exposure controls were recruited. We showed that the ratio of activated CD4 + T cells (downregulation of CD62 L) was dramatically increased in OMLDT patients compared to exposure and non-exposure control, suggesting that CD4 + T cells activation was a key cellular event in the development of OMLDT. In parallel, the expression of cytokine including IL-2, IFN-γ, TNF-α and IL-17A were increased obviously and IL-4 decreased in CD4 + T cells from OMLDT patients. in vitro assay, we found that trichloroethylene metabolites trichloroacetaldehyde (TCAH), not trichloroacetic acid (TCA) or Trichloroethanol (TCOH) could activate the naïve CD4 + T cells characterized by a rise in intracellular calcium, down-regulated CD62 L and subsequently trigger the secretion of IL-2, IFN-γ and TNF-α. Notably, the phosphorylation status of NF-κB and p38MAPK were elevated in OMLDT patients. Moreover, TCAH also could activate the p38MAPK and NF-κB, suggesting the role of p38MAPK and NF-κB pathways in the activation of CD4 + T cells. In addition, we found that the inhibition of Schiff base formation decreased the ability of TCAH to induce the activation of naïve CD4 + T cells and p38MAPK and NF-κB pathway. In conclusion, we revealed that the CD4 + T activation and increased the cytokines including IL-2, IFN-γ and TNF-α but decreased IL-4 in CD4 + T cells were associated with OMLDT. TCAH could activate naïve CD4 + T cells through NF-κB and p38MAPK activation induced by Schiff base formation, which might contribute to the development of OMLDT. These findings provide a new insight into the pathogenesis of OMLDT.